Comparative effectiveness and safety of DPP-4 inhibitors - Mamza, Jil Billy (2016)
Approximately 3 million people throughout the UK suffer with Type 2 diabetes mellitus (T2DM), and are 32% more likely to die early. There remains a lack of evidence for the long-term effectiveness and safety of anti-diabetic drugs in preventing diabetes-related complications, making it unclear how to optimally manage diabetes. Work to date includes observational studies subject to bias, and randomised controlled trials (RCTs), which may not reflect the ‘real world’ situation. The aim of this thesis is to combine such findings via systematic reviews, meta-analyses and retrospective cohort studies to provide more water-tight evidence of the effectiveness and safety of glucose-lowering therapies (GLT) in the long term.